Alamethicin Supramolecular Organization in Lipid Membranes from (19)F Solid-State NMR - Salnikov, Evgeniy S. (Biophys J, 2016)
Alamethicins (ALMs) are antimicrobial peptides of fungal origin. Their sequences are rich in hydrophobic amino acids and strongly interact with lipid membranes, where they cause a well-defined increase in conductivity. Therefore, the peptides are thought to form transmembrane helical bundles in which the more hydrophilic residues line a water-filled pore. Whereas the peptide has been well characterized in terms of secondary structure, membrane topology, and interactions, much fewer data are available regarding the quaternary arrangement of the helices within lipid bilayers. A new, to our knowledge, fluorine-labeled ALM derivative was prepared and characterized when reconstituted into phospholipid bilayers. As a part of these studies, C(19)F(3)-labeled compounds were characterized and calibrated for the first time, to our knowledge, for (19)F solid-state NMR distance and oligomerization measurements by centerband-only detection of exchange (CODEX) experiments, which opens up a large range of potential labeling schemes. The (19)F-(19)F CODEX solid-state NMR experiments performed with ALM in POPC lipid bilayers and at peptide/lipid ratios of 1:13 are in excellent agreement with molecular-dynamics calculations of dynamic pentameric assemblies. When the peptide/lipid ratio was lowered to 1:30, ALM was found in the dimeric form, indicating that the supramolecular organization is tuned by equilibria that can be shifted by changes in environmental conditions.